Konektivitasi Hate Speech, Hoaks, Media Mainstream dan Pengaruhnya Bagi Sosial Islam Indonesia - Luqman Al Hakim; Said Hafif Anshori (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article aims to explain the connections between hate speech, hoaxes, mainstream media with impact on Indonesian Social Islam. the article will explain the role media in developing in the social field, and technology until giving new perusal, in problems in related actual issues until becoming rich perspective and understand information. The mapping in this paper is described from the 2014 Presidential Election to the issues that have been circulating recently, including the development of the dynamics of Indonesian Islam. The solutions presented in this paper are; the role of parents in controlling their children and early social media education. This must be done because the current generation is a generation that is aware of technology, thus it is appropriate to educate based on the needs of the times. There are results found that there are deficiencies in understanding and applying social media so that it often creates anxiety that starts from the virtual world and then is brought to the real world or vice versa from the real world to the virtual world.